IMPORTANCE OF DIRECT INVESTMENT IN THE COUNTRY’S ECONOMY: THEORY AND PRACTICE (World Economics and Finance Bulletin, 2024)
This article examines the essence of the attractiveness of the investment climate, the theory of international indices recognized by the world, which assesses the investment potential, the views of economists on increasing investment attractiveness in attracting foreign investment. At the same time, the methods of determining the investment flow of developed countries, the negative and positive factors affecting investment attractiveness are analyzed. In addition, the necessary mechanisms for attracting foreign investment and scientific conclusions and recommendations to increase investment attractiveness have been developed.If we want to increase the volume of foreign investment, it is necessary to increase the investment potential of enterprises, regional conditions and conditions to a more acceptable and higher level than others (competitors), as well as to stimulate domestic (national) investment. we need to focus on ensuring that it is holistic.
Keywords: enterprise risk; investment potential of the enterprise; investment climate